Islamic Education in a Pluralistic Society - Nuryatno, M. Agus (Al-Jamiah: Journal of Islamic Studies, 2011)
The focus of this paper concerns how to construct an Islamic education that corresponds to a pluralistic society like Indonesiaâs. To answer this question it refers to a theory of religious education that consists of three models: in, at, and beyond the wall. Religious education in the wall is a model of religious education thatâs only concern is with its own religion, without connecting it with other religions. The second model is religious teaching at the wall, where students are not only taught about their own religion but is also connected with other religions. The last model is religious education beyond the wall, which means helping students to work together with people of other faiths for peace, justice, and harmony. From these models, the dominant practice of Islamic education is based on the first model, religious teaching in the wall. For this reason, I shall argue that it is necessary to shift the model of Islamic teaching from in to at and beyond the wall, in order for Muslim students to not ignorant of other religions and to make them able to work together with other students of different faiths to combat the common enemy of religions such as violence, poverty, corruption, manipulation, and the like. To make Islamic teachers capable of implementing this model of religious teaching, it is necessary to have types of religiosity that correspond to it, namely inclusive-pluralist religiosity, critical-reflective religiosity, multicultural religiosity, humanist religiosity, and social-active religiosity.[Pertanyaan inti yang hendak dijawab melalui artikel ini adalah bagaimanamengkonstruk pendidikan Islam yang sesuai dengan masyarakat plural seperti Indonesia. Untuk menjawab pertanyaan tersebut, penulis merujuk teori pendidikan agama yang terdiri dari tiga model: in, at, dan beyond the wall. Pendidikan agama in the wall adalah model pendidikan agama yang hanya memperhatikan agama sendiri tanpa mendialogkan dengan agama yang lain. Model kedua, pendidikan agama at the wall, tidak hanya mengajar siswa tentang agama mereka sendiri, tapi juga agama yang lain. Model terakhir adalah pendidikan agama beyond the wall, yang membantu siswa untuk bekerjasama dengan siswa lain meski berbeda agama demi tegaknya perdamaian, keadilan, dan harmoni. Dari ketiga model ini, praktek dominan pendidikan Islam didasarkan pada model pertama, yaitu pendidikan agama in the wall. Untuk itu penulis berargumen bahwa sudah saatnya untuk menggeser model pendidikan agama dari in ke at dan beyond the wall, agar siswa Muslim tahu dan kenal akan agama yang lain dan menjadikan mereka mampu bekerjasama dengan siswa lain yang memeluk agama berbeda dengan tujuan memerangi musuh utama agama, yaitu kekerasan, kemiskinan, korupsi, manipulasi, dan sejenisnya. Agar guru-guru agama Islam mampu menerapkan model pendidikan agama seperti ini, maka mereka perlu memiliki model-model keagamaan yang sesusai dengan spirit tersebut, seperti model keagamaan inklusif-pluralis, kritis-reflektif, multikultural, humanis, dan aktif-sosial.]